Effect of foot reflexology on chronic pain in Parkinson’s disease: A randomized controlled trial - Karel Joineau; Estelle Harroch; Mathilde Boussac; Margherita Fabbri; Clémence Leung; Fabienne Ory-Magne; Vanessa Rousseau; Patrice Peran; Christine Brefel-Courbon; Emeline Descamps (PLoS ONE, 2025)
Objectives Effectiveness of Foot Reflexology (FR) on the pain intensity in Parkinson’s disease (PD) compared with Sham Massage (SM). Design Monocentric, longitudinal, prospective, double-blind, randomized controlled trial. Randomization with a random number generator in the R software. Fixed-sized block randomization of 3 implemented into Clinsight. Participants Idiopathic PD patients with chronic pain (Visual Analogue Scale (VAS)≥4) were recruited from the Toulouse University Hospital between the 14th of April 2021 and the 25th of May 2025. Intervention Four one-hour long FR or SM sessions three weeks apart with the same specialized FR researcher. Main outcome measure Pain intensity change measured by the mean VAS before and after full completed interventions. The difference was compared between group using a Wilcoxon Mann Witney test. Exploratory outcome: brain functional connectivity Results 30 PD patients were randomized and analyzed. Interventions were delivered as planned for all patients. Clinical variables did not significantly differed between FR and SM groups. Mean VAS decreased by −12.3 mm ± 15.2 in FR group (n = 15) and −17.9 mm ± 29.4 in SM group (n = 15). Analyses did not reveal any significant difference between the FR and SM groups (p-value = 0.88). There are different patterns in connectivity changes in the medial pain system between responders (at least 30% pain reduction) and non-responders to both therapies. There were no adverse events. Conclusion FR is not more effective than SM in relieving chronic pain in PD. The differences in connectivity patterns within the medial pain pathway may underlie the response to tactile stimulation (FR and SM). Trial registration ClinicalTrials.gov NCT04705207.